Case report - Adrenal collision tumour composed of oncocytoma and pheochromocytoma - Lukic, Jovana; Ilic, Sanja; Zivic, Rastko; Mitic, Stefan; Savic, Predrag; Vukomanovic, Vladan; Petrovic, Milos (Frontiers in Oncology, 2025)
Adrenal collision tumours (ACTs) are rare clinical entities denoting separate coexisting tumours involving adrenal glands. Here, we report the clinical, radiological and pathohistological presentation of a 49-year-old patient with an ACT composed of oncocytoma and pheochromocytoma. Following the initial diagnostic procedure guided by suspicion of pheochromocytoma, the patient has undergone surgery, recovered well and has been followed since. In the resected mass, oncocytoma was an incidental finding, as is typical of this type of tumour. With both components of this particular ACT being rare, this is a reminder of a need for widening differential diagnostic options when evaluating the patient for adrenal masses of unknown origin.